Operator method in diffraction by semi-infinite graphene grating - Калиберда, М.Е.; Литвиненко, Л.Н.; Погарский, С.А. (Radiotekhnika, 2019)
Diffraction of the H- polarized plane electromagnetic wave in the THz range by the semi-infinite graphene strip grating is considered. The non-linear operator equation relatively unknown reflection operator of the structure is presented. The reflection operator of a single graphene strip is obtained with the use of the method of singular integral equations. The dependencies of the total scattering cross section as well as field patterns at the plasmon resonance frequency are represented.